Implementation of an antimicrobial stewardship programme in three regional hospitals in the south-east of Liberia: lessons learned. Issue 3 (24th June 2022) - Alabi, Abraham S; Picka, Stephen W; Sirleaf, Reubvera; Ntirenganya, Pacifique R; Ayebare, Arnold; Correa, Nidia; Anyango, Sarah; Ekwen, Gerald; Agu, Emmanuel; Cook, Rebecca; Yarngrorble, John; Sanoe, Ibrahim; et al.
Abstract: Background: Antimicrobial stewardship (AMS) programmes can improve the use of antimicrobial agents. However, there is limited experience in the implementation of such programmes in low- and middle-income countries (LMICs). Objectives: To assess the effect of AMS measures in south-east Liberia on the quality of antimicrobial use in three regional hospitals. Methods: A bundle of three measures (local treatment guideline, training and regular AMS ward rounds) was implemented and quality indicators of antimicrobial use (i.e. correct compounds, dosage and duration) were assessed in a case series before and after AMS ward rounds. Primary endpoints were (i) adherence to the local treatment guideline; (ii) completeness of the microbiological diagnostics (according to the treatment guideline); and (iii) clinical outcome. The secondary endpoint was reduction in ceftriaxone use. Results: The majority of patients had skin and soft tissue infections ( n  = 108) followed by surgical site infections ( n  = 72), pneumonia ( n  = 64), urinary tract infection ( n  = 48) and meningitis ( n  = 18). After the AMS ward rounds, adherence to the local guideline improved for the selection of antimicrobial agents (from 34.5% to 61.0%, P  < 0.0005), dosage (from 15.2% to 36.5%, P  < 0.0005) and duration (from 13.2% to 31.0%, P  < 0.0005). In total, 79.7% of patients (247/310) had samples sent for microbiological analysis. Overall, 92.3% of patients improved on Day 3 (286/310). The proportion of patients receiving ceftriaxone was significantly reduced after the AMS ward rounds from 51.3% to 14.2% ( P  < 0.0005). Conclusions: AMS measures can improve the quality of antimicrobial use in LMICs. However, long-term engagement is necessary to make AMS programmes in LMICs sustainable.